Cambio de área glaciar en el volcán Maipo (Andes Centrales), una aproximación morfométrica: 4 décadas de registros satelitales - Lo Vecchio Repetto, Andrés (2022)
Current climatic conditions in Central Andes (CA) (31-36° S) have triggered the reduction of glacier area. Although CA are geographically circumscribed to an area under the same macroclimatic domain, their rugged topography creates several topoclimates as response to the effects of elevation, slope and aspect (morphometric factors). This study explores the impact of morphometric factors on the evolution of the glacial surface located above of Maipo volcano (34°09’50’’ S; 69°49’53’’ W). Through the use of 11 LANDSAT images (MSS, TM and OLI), the spatiotemporal evolution of the glacier area was reconstructed (period 1976-2020). On this period, glacier area was reduced by 6±0.5 km2 (-0.14±0.01 km2a-1), equal to 63% of 1976 glacial area (9.6±0.5 km2). Fifty percent of the reduction occurred between 3,900 and 4,400 m elevation, with absolute losses towards lower elevations. In addition, it was detected that for every 100 m of ascent the relative area loss rate decreased 0.1 %a-1 (R2=0.81; p-value<0.05). Also, it was observed that south’s glacial surface (SE and SW too) concentrated between two and three times more surface area than the rest. There, the greatest loss glacier’s area took place (1.3 km2), although in relative terms it represented 55% of the initial area (0.9%a-1). On the contrary, north slope’s glacial surface was disappeared. Glacial area’s change as an elevation function showed the largest differences against glacial area’s total change, suggesting the difficulty of assuming mean elevations as descriptors of glacial change, especially at elevations higher than 4,700 m. The reduction of uncovered glaciers located on the steep slopes of the Maipo volcano has led to an increase in debris on the remaining glacier surface and the expansion of covered glaciers.